2021
DOI: 10.1038/s41598-021-02586-4
|View full text |Cite
|
Sign up to set email alerts
|

An improved 2-level MPPT scheme for photovoltaic systems using a novel high-frequency learning based adjustable gain-MRAC controller

Abstract: Under rapidly changing environmental conditions, the model reference adaptive control (MRAC) based MPPT schemes need high adaptation gain to achieve fast convergence and guaranteed transient performance. The high adaptation gain causes high-frequency oscillations in the control signals resulting in numerical instability and inefficient operation. This paper proposes a novel high-frequency learning-based adjustable gain MRAC (HFLAG-MRAC) for a 2-level MPPT control architecture in photovoltaic (PV) systems to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Figure 24 shows the PV current vs. load current, and Figure 25 shows the PV voltage vs. load voltage in all the states. Table 2 36) and (37).…”
Section: Case Iv: Robustness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 24 shows the PV current vs. load current, and Figure 25 shows the PV voltage vs. load voltage in all the states. Table 2 36) and (37).…”
Section: Case Iv: Robustness Testmentioning
confidence: 99%
“…MRAC architecture aims to critically dampen reaction. It is an adaptive controller that matches the plant model's to reference model's response even if plant parameters vary or are unclear 37 . Figure 9 depicts the block representation of the MRAC model.…”
Section: Design Of Proposed Inc‐mrac Techniquementioning
confidence: 99%
“…[26]. A small-signal equivalent circuit is assumed to simplify the study of transient response as indicated in [27]. Figure 5 displays the small-signal equivalent circuit of PV.…”
Section: Boost Converter Dynamicsmentioning
confidence: 99%